Preparation of preschool teachers during the COVID-19 pandemic: an online professional development program in STEM education - Yıldırım, Bekir (Routledge Journals, Taylor & Francis Ltd, 2023)
BackgroundThis study investigated how an online professional development program (OPDPs) affected preschool teachers' STEM teaching competence, what technological tools and materials they used during STEM education after the program, and what they thought about OPDPs.PurposeThis study aimed to focus on all dimensions of the effects of OPDPs on the professional development of preschool teachers in STEM educationSampleThe sample consisted of 41 public or private school preschool teachers (33 women and eight men) with different experiences.Design and methodParticipants were recruited using purposive criterion sampling. The study adopted a mixed embedded design. Quantitative data were analyzed using paired sample t-test, Wilcoxon signed-rank test, and effect size. The qualitative data were analyzed using inductive content analysis. Lesson plans were analyzed using descriptive statistics.ResultsThe program help participants develop the competence to deliver STEM classes. It also helped them positive attitudes toward OPDPs. After the program, participants used more tools and materials (technological materials, daily-life materials, computer-free coding materials, Lego sets, etc.) in their lectures. Recommendations were made based on the results.
Keywords: Preschool Teachers; Stem Education; Online Professional Development; Covid-19; Science; Technology; Beliefs; Mathematics; Perceptions; Integration; Engagement; Experience; Learners; Robotics